Remimazolam Suppresses Oxidative Stress and Apoptosis in Cerebral Ischemia/Reperfusion Injury by Regulating AKT/GSK-3β/NRF2 Pathway - Duan M; Yu N; Liu J; Zhao Y; Zhang J; Song S; Wang S (Drug Design, Development and Therapy)
Mei Duan,1,* Ning Yu,1,* Jia Liu,1 Yang Zhao,1 Jing Zhang,1 Siyi Song,2 Shilei Wang1 1Department of Anesthesiology, The Affiliated Hospital of Qingdao University, Qingdao, People’s Republic of China; 2Department of Anesthesia and Perioperative Medicine, The First Affiliated Hospital of Shandong First Medical University, Jinan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shilei Wang, Department of Anesthesiology, The Affiliated Hospital of Qingdao University, Qingdao, People’s Republic of China, Tel +86 186 6180 6773, Email wshlei@aliyun.comIntroduction: The mechanism of remimazolam, a benzodiazepine that activates γ-aminobutyric acid a (GABAa) receptors, in cerebral ischemia/reperfusion (I/R) injury is not well understood. Therefore, we explored whether remimazolam activates protein kinase B (AKT)/glycogen synthase kinase-3β (GSK-3β)/nuclear factor erythroid 2-related factor 2 (NRF2) to attenuate brain I/R injury in transcerebral I/R-injured rats and transoxygenic glucose deprivation/reperfusion (OGD/R)-injured SY5Y cells.Material and Methods: Remimazolam was added at the beginning of cell and rat reperfusion, and the PI3K/AKT inhibitor LY294002 was added to inhibit the AKT/GSK-3β/NRF2 pathway 24 h before cellular OGD/R treatment and 30 min before rat brain I/R treatment. The viability and apoptosis rate of SY5Y cells, neurological deficit score, cerebral infarction volume and morphological changes of rat brain cells as well as the protein expression of Bax, Bcl2, Caspase 3, Cleaved-Caspase 3 and the number of TdT-mediated dUTP Nick-End Labeling (TUNEL)-positive cells in the penumbral region were detected. Reactive oxygen species (ROS), malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), NRF2, heme oxygenase 1 (HO-1), AKT, P-AKT, GSK-3β, P-GSK-3β protein expression, and nuclear translocation of NRF2 were measured in cell and animal assays.Results: Reduced SY5Y cell viability and increased apoptosis caused by OGD/R injury, elevated neurological deficit scores and cerebral infarct volume induced by brain I/R injury in rats, cerebral cell injury, as well as elevated Bax, Cleaved-Caspase 3, decreased Bcl2, and increased number of TUNEL-positive cells in rat brain tissue were all moderated by remimazolam. Decreased GSH-Px, SOD and Elevated MDA, ROS induced by OGD/R-injured SY5Y cells and brain I/R-injured rats were moderated by remimazolam. Meanwhile, remimazolam increased NRF2, HO-1, P-AKT, P-GSK-3β, and the nuclear accumulation of NRF2. The PI3K/AKT inhibitor LY294002 reversed the role of remimazolam in brain I/R injury.Conclusion: This study demonstrates that remimazolam activates the AKT/GSK-3β/NRF2 pathway, thereby attenuating oxidative stress and apoptosis to protect against brain I/R injury.Keywords: remimazolam, AKT/GSK-3β/NRF2 signaling pathway, ischemia-reperfusion injury, apoptosis, oxidative stress